1981
DOI: 10.3382/ps.0600393
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Color, Trypsin Inhibitor Contents, and Urease Index of Soybean Meal and Effects on Broiler Performance

Abstract: Three experiments were conducted to determine the relationships between trypsin inhibitor contents, urease index, and color of soybean meal, and the effect on broiler performance. Either 0, 8, 10, 12, 14, or 16% moisture (Experiment 1) or 0, 2, 4, 6, 8, or 10% moisture (Experiment 2) was added after dehydrating raw, flaked, solvent-extracted soybeans to 2% moisture. Each sample was then sealed in .473-liter jars, autoclaved for 0 to 135 min, with 15-min intervals, and dried at 37 C in a vacuum oven to remove a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…As heat treatment inc~ased from 5 to 20 min, final pig weight was increased (21.1 vs 14.9 kg), and as heat treatment was increased further to 60 min, final weight was decreased to 17.8 kg. This quadratic effect of heat treatment is consistent with responses reported previously from experiments with rats (Klose et al, 1946;Borchers, 1965;Hancock et al, 199Ob), chickens (Clandinin et al, 1948;McNaughton et al, 1981) and pigs (Heinz and Poppe, 1975;Gmen et al, 1982).…”
Section: Resultssupporting
confidence: 80%
“…As heat treatment inc~ased from 5 to 20 min, final pig weight was increased (21.1 vs 14.9 kg), and as heat treatment was increased further to 60 min, final weight was decreased to 17.8 kg. This quadratic effect of heat treatment is consistent with responses reported previously from experiments with rats (Klose et al, 1946;Borchers, 1965;Hancock et al, 199Ob), chickens (Clandinin et al, 1948;McNaughton et al, 1981) and pigs (Heinz and Poppe, 1975;Gmen et al, 1982).…”
Section: Resultssupporting
confidence: 80%
“…It was observed that in 25 min the outlet moisture content varies between 170 and 43 g/kg depending on the initial moisture content and treatment temperature. As regards the inactivation process, a urease assay 'pH increase' of less than 0.15 is considered sufficient, based on adequate heat treatment for animal feed and edible soy flours (12). Soybean processing plants typically use a urease index of 0.2 pH increase to indicate adequate heat processing (13,14).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DDGS samples were analyzed for ash, starch (Directive 1999/79 CE), CP (NF V18-120), crude fat (NF V18-117), crude fiber (NF V03-040) and NDF, ADF and ADL (NF V18-117). Finally, DDGS lightness score (L) was measured using a CR-410 colorimeter (Konica Minolta illuminate D65) as described by McNaughton et al (1981). L score vary from 0 = black to 100 = white.…”
Section: Chemical Analysesmentioning
confidence: 99%